Planktonic Tintinnid Community Structure Variations in Different Water Masses of the Arctic Basin - Wang, Chaofeng; Wang, Xiaoyu; Xu, Zhiqiang; Hao, Qiang; Zhao, Yuan; Zhang, Wuchang; Xiao, Tian (Frontiers in Marine Science, 2022)
Information on tintinnid community structure variations in different water masses in the Arctic Basin were scarce. During the summer of 2020, tintinnid diversity and vertical distribution were investigated in the Arctic Ocean. A total of 21 tintinnid species were found in five water masses and each water mass had unique tintinnid community structure. In the Pacific Summer Water (PSW), Salpingella sp.1 occupied top abundance proportion (61.8%) and originated from the North Pacific. In the Remnant Winter Water (RWW), Acanthostomella norvegica occupied top abundance proportion (85.9%) and decreased northward. In the Mixed Layer Water, Pacific Winter Water and Atlantic-origin Water, Ptychocylis urnula had highest abundance proportion (67.1%, 54.9% and 52.2%, respectively). High abundance distribution area of Salpingella sp.1 and A. norvegica was separated by boundary of the Beaufort Gyre and Transpolar Drift. These above species might can regarded as indicator species of each water masses. Highest abundance proportion of Salpingella sp.1 contribute 81.9% to dominance of 12–16 μm lorica oral diameter in the PSW, which indicated that preferred food items of tintinnid was also getting smaller. The occurrence of North Pacific tintinnid in the PSW might be due to the increasing Pacific Inflow Water. Further study were needed to explore lasting period of this species and whether it can establish local population under rapid Arctic warming progress.